Dakwah Inklusif dalam Kerangka Maqāṣid Al-Sharī’ah: Studi Kasus Pola Interaksi Lintas Agama pada Masyarakat Kalukku (Inclusive Dakwah in The Framework of Maqāṣid Al-Sharī'ah: A Case Study of Cross-Religious Interaction Patterns in Kalukku Community) - Muliadi Muliadi; A. Zamakhsyari Baharuddin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This study aims to elaborate and analyze the harmonization model of religious life which is integrated into the patterns of religious social interaction in Kalukku and the role of religious leaders in knitting religious social harmony. The method applied is a qualitative method using inductive data analysis. The results of this study indicate that the pattern of religious interaction in Kalukku refers to the three patterns of Hossein Nasr interaction, namely: 1) concentric interaction patterns; 2) reciprocal interaction patterns; and 3) bound interaction patterns, which are carried out in an integrated manner have succeeded in creating a dynamic, harmonious and quality model of religious interaction. The motivation that underlies the realization of an energetic relationship refers to the concept of the four pillars of maqāṣid Ibn ‘Āshūr namely Fiṭrah, Samāḥa, al-Musāwāh, and Ḥurriyah. The paradigm of religious leaders towards the existence of cross-faith parties leads to a tolerant attitude based on the concept of Cak Nur's inclusive theology. The harmony and tolerant paradigm in Kalukku is built through formal and non-formal da'wah which is woven in efforts to acculturate religion and culture.